CTNI-13. UPDATES ON CLINICAL OUTCOMES AND TUMOR RECURRENCE PATTERNS OF A HUMAN PILOT STUDY ASSESSING EFFICACY OF BELINOSTAT (PXD-101) COMBINING WITH CHEMORADIATION IN TREATING GLIOBLASTOMA. (9th November 2020) - Xu, Karen; Huang, Vicki; Ramesh, Karthik; Gurbani, Saumya; Schreibmann, Eduard; Weinberg, Brent; Sengupta, Soma; Voloschin, Alfredo; Holdhoff, Matthias; Barker, Peter; Kleinberg, Lawrence; Olson, Jeffrey; et al.
Abstract: INTRODUCTION: Glioblastoma (GBM) is highly aggressive with poor prognosis. Belinostat is a histone deacetylase inhibitor with blood–brain barrier permeability that has anti-GBM activity and may enhance effects of chemoradiation. Our institution conducted a clinical trial evaluating clinical efficacy of belinostat with standard-of-care therapy for GBMs. METHODS: 13 and 14 patients were enrolled into cohort 1 (c1, control) or cohort 2 (c2, belinostat) with 12 in each group with sufficient follow-up MRIs for recurrence analysis. All patients received concurrent, adjuvant temozolomide and focal radiation therapy (RT). For c2 patients, the belinostat regimen (500-750mg/m 2 1x/day x 5 days) was given over three cycles every 3 weeks (weeks -1, 2, and 5 of RT). RT margins of 5–10 mm and 3 mm were added to generate clinical tumor volumes and planning target volumes (PTVs). PTV1 (based on FLAIR MRI) and PTV2 (based on CE-T1w MRI) received 51 and 60 Gy, respectively, over 30 fractions. Volume at initial recurrence (rGTV) was contoured. RESULTS: Mean age was 58.3 years for c1 and 51.1 years for c2. Patient/tumor characteristics were similar between cohorts. Median OS were 16.6 and 18.5 months for c1 and c2 (p=0.538), respectively. Average minimum, maximum and mean radiation dose to rGTV was 54.1 Gy, 64.2 Gy and 62 Gy, for c1, and 47.5 Gy, 57.6 Gy and 53.5 Gy, for c2 (p=0.322, 0.088 and 0.071), respectively. The mean overlap between rGTV and PTV1/PTV2 for c1 & c2 were 99.2% & 96.9%/99.8% & 78.7% (p=0.489/0.133), respectively. CONCLUSION: Median OS was slightly longer for c2 though not statistically significant. rGTV in c1 received higher radiation doses and had more overlap with PTV2 than in c2. Out-of-field recurrence appears more likely in c2 suggesting better infield control with belinostat. This study highlights the potential of belinostat as a synergistic therapeutic agent for GBM treatment.